Implementation of Radio Convergence of The Republic of Indonesia (RRI Pro 1 Yogyakarta) in Maintaining Existence in The Digital Era - Adit Saputra; Angga Intueri Mahendra (PT Mattawang Mediatama Solution, 2024)
In a modern era as it is today, technology is developing very rapidly, so the media industry must also grow.The mass media, especially radio, must go hand in hand with globalization and the Internet to survive, let alone society has shifted from digital media to conversional, so convergence is a solution to keep radio heard by the public. Media convergence is the integration of the traditional telecommunications media with the Internet. The Radio of the Republic of Indonesia (RRI) is the only radio station owned by the State of the Union of Indonesia. (NKRI). The aim of this research is to know and explain the form of Yogyakarta RRI strategy inining its existence in the digital age. The theory used in this study is Henry Jenkins' theory by uniting the 3c of computing, communication, and content. The study uses qualitative methods and participant observation. The results of this study found that the step RRI Yogyakarta took to preserve its existence in this digital age was by making convergence. Convergence carried out by RRI Yogyakarta among others Website, RRI Go Play, Chanel Youtube and RRI Net. The impact of the convergence done by Yogyakarta RRI is the ease of access, the public can access and can enjoy through smartphone anywhere and anytime.